CHALLENGES OF TRANSLATION - Egamberdiyeva Iroda Abdurahimovna; Toshtemirova Nilufarkhon Ashurali kizi (TADQIQOTLAR, 2025)
Abstract:  Translation,  a  fundamental  act  of  cross-cultural  communication, involves  transferring  meaning  from  one  language  into  another  while  preserving linguistic,  cultural,  and  contextual  nuances.  Despite  technological  advancements, translators  still  face  multifaceted  challenges  ranging  from  linguistic  differences  to cultural  disparities  and  domain-specific  complexities.  This  article  explores  the principal  challenges  encountered  in  translation,  including  lexical  gaps,  idiomatic expressions,  syntactic  variations,  cultural  references,  and  technical  language. Additionally,  it  discusses  the  impact  of  machine  translation  and  the  importance  of human intuition in the process. The study emphasizes the need for skilled translators with  interdisciplinary  knowledge  and  cultural  sensitivity  to  ensure  effective communication across languages.